1994
DOI: 10.1002/stem.5530120203
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 12: A key modulator of immune function

Abstract: Interleukin (IL)-12 was cloned on the basis of its ability to activate natural killer (NK) cells and promote the development of cytolytic T cells. With further understanding of its activities, IL-12 has emerged as an important cytokine, affecting both immune and hematologic functions. It has been shown to be necessary for the T cell independent induction of interferon (IFN)-gamma, critical for the initial suppression of bacterial and parasitic infection; for the development of a Th1 response, critical for effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
1
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(99 citation statements)
references
References 58 publications
2
95
1
1
Order By: Relevance
“…14 It is also known that IL-12 releases into the culture medium large 5). Unlike in our previous study, 16 we did not observe any significant increase in the number of CFU-GM after incuamounts of ␥-IFN, [16][17][18][19][20] a cytokine with potent antiproliferative activity. These characteristics, together with the fact that NKbation with IL-2.…”
Section: Clonogenic Assaycontrasting
confidence: 89%
See 1 more Smart Citation
“…14 It is also known that IL-12 releases into the culture medium large 5). Unlike in our previous study, 16 we did not observe any significant increase in the number of CFU-GM after incuamounts of ␥-IFN, [16][17][18][19][20] a cytokine with potent antiproliferative activity. These characteristics, together with the fact that NKbation with IL-2.…”
Section: Clonogenic Assaycontrasting
confidence: 89%
“…[14][15][16] It has been shown to cause the proliferation USA) with 10% human AB serum (Flow ICN Biomedicals, of activated T and NK cells, to enhance the lytic activity of NK Costa Mesa, CA, USA), whereas the BMMNC were resuscells and to induce the production of antileukemic cytokines, pended at the same concentration in IMDM (Life particularly ␥-IFN. [16][17][18][19][20] In a previous study, we demonstrated Technologies) with 10% FCS (Hyclone Laboratories, Logan, that the defective bone marrow (BM) and peripheral blood UT, USA). RhIL-12 (Sigma-Aldrich, Milan, Italy) at a concen-(PB) NK-activity in MDS patients can be restored in vitro by tration of 0.1 ng/ml with or without RhIL-2 (Proleukin; Cetus the addition of another immunoregulatory cytokine, IL-2.…”
mentioning
confidence: 99%
“…In general, IL-12 upregulates interferon (IFN)-g production by T cells and natural killer cells, promotes Th1 responses, and suppresses the expression of Th2 cytokines. 17,18 A previous study showed that production of IFN-g in combination with IL-10 was induced in T cells by 20 Furthermore, this combined production of IFN-g and IL-10 was postulated to occur in immunoregulatory T cells that protect against severe inflammatory pathologies. 21 Recently, it was shown that sublingual immunotherapy with a Dermatophagoides monomeric allergoid downregulated allergen-specific IgE and was associated with a significant increase in T cells producing both IL-10 and IFN-g. 22 In addition, an inducible Th1-like Treg cell, which produces both IL-10 and IFN-g, was reported to block the development of allergen-induced AHR in a murine model of asthma.…”
Section: Introductionmentioning
confidence: 99%
“…This particular cytokine has numerous effects on the immune system including stimulation of NK activity, and induction of the production of interferon gamma. 8 The ability of IL-12 to enhance the effect of IL-2 on NK activity, as shown in our combination experiments with IL-2 and IL-12, may be related to the synergistic effect of these two cytokines on the production of gamma interferon. 14 Figures 3 to 5 illustrate the results of our experiments when anti-gamma interferon was added simultaneously to the effec- IL-12 inhibition with anti-gamma interferon.…”
Section: Figurementioning
confidence: 63%
“…IL-12 activates cytotoxic lymphocytes and natural killer cells and also induces interferon gamma production. 7,8 It has demonstrated activity against solid tumor cell lines and murine solid tumor xenograft models. [9][10][11] Recently, reports have documented anti-leukemia effects as well.…”
Section: Introductionmentioning
confidence: 99%